A Comparison of the Motifs on Kelantan and Yunnan Silverware - Guo Che; Azhari Md Hashim (Environment-Behaviour Proceedings Journal, 2025)
This study provides an in-depth analysis of the similarities and differences between the handicraft silverware motifs of Kelantan and Yunnan, with a particular focus on the silverware handicraft artefacts of Kota Bharu, Kelantan and Dali, Yunnan, emphasizing the structural elements of the decorative motifs. Focusing on the diversity of motif classifications, visual representations and motifs exhibited in the two regions, comparative analyses are needed to identify similarities and differences in thematic content. This study deepens our understanding of the differences in the motifs of handcrafted silverware from different regions, demonstrating how this culturally significant tradition is shown through motifs.